A Modern AI-Integrated Methodology for Improving Writing Skills in English Language Learning - Odilova , Mukhlisa (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis investigates a modern approach to improving writing skills in English as a Foreign Language (EFL) contexts through an AI-integrated instructional methodology. Writing remains one of the most challenging skills for learners due to limited exposure, lack of feedback, and insufficient practice opportunities. Traditional and process-based methods are often not sufficient to develop learners’ complexity, accuracy, and fluency (CAF). Therefore, this study proposes the AI-Integrated Multimodal Writing Methodology (AIMMWM), which combines artificial intelligence tools, collaborative learning, adaptive feedback systems, and multimodal composition practices. The aim of this methodology is to enhance learner autonomy, engagement, and writing performance. The thesis is based on theoretical research and recent studies in second language acquisition and educational technology. It argues that AI-supported writing instruction significantly improves learner outcomes by providing personalized, immediate, and continuous feedback.